Feminist Theory Reveals a Need for Justice over Autonomy in Research Ethics - Alix E. Masters (Voices in Bioethics, 2018)
Informed consent has remained one of the more debated topics within research ethics.  Many scholars and bioethicists have wondered the best way to obtain it, who should give it, and if it is even necessary at all.  Feminist scholarship has remained similarly engaged in questions surrounding consent, with particular focus on sex and sexuality. This year, in the wake of the #MeToo movement, we have witnessed a cultural shift towards a willingness to address the perils of sexual consent under patriarchy.  In the context of this cultural reckoning, I see no better time to apply feminist epistemology to the fraught nature of consent to a bioethical framework. Feminist bioethicists, such as Susan Sherwin, have long argued for a wider consent model that privileges justice over a focus on autonomy.  Using radical feminist theorist Catherine MacKinnon’s work on consent and sexual harassment, I will support Sherwin’s claim by arguing for a more nuanced understanding of power and structural social hierarchy that exists in every aspect of our society, including research.